2015
DOI: 10.1155/2015/264528
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Foot-and-Mouth Disease Virus in Buffaloes (Syncerus caffer) in Zambia

Abstract: A study was conducted to determine the serotypes of foot-and-mouth disease viruses (FMDV) circulating in African buffaloes (Syncerus caffer) from selected areas in Zambia. Sera and probang samples were collected between 2011 and 2012 and analysed for presence of antibodies against FMDV while probang samples were used to isolate the FMDV by observing cytopathic effect (CPE). Samples with CPE were further analysed using antigen ELISA. High FMD seroprevalence was observed and antibodies to all the three Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Actually, buffaloes maintain FMD infections and infect other susceptible species in Sub-Saharan Africa [ 35 ]. Natural and experimental transmission of FMD from carrier buffalo to cattle was confirmed [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, buffaloes maintain FMD infections and infect other susceptible species in Sub-Saharan Africa [ 35 ]. Natural and experimental transmission of FMD from carrier buffalo to cattle was confirmed [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The viral particles present in all discharges and secretions of sick animals, so the virus spreads efficiently. Infection occurs through the exposure to the contaminated materials either directly or indirectly [ 8 ]. Control of FMD infection is so difficult as the wind can spread the virus for a distance of 10 km [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recombination is believed to be dependent upon simultaneous replication of distinct viruses within the same cell, co-occupying the same replication complex. Numerous studies, especially in African countries have reported serological evidence of individual animals infected by multiple FMDV serotypes [43][44][45][46][47][48] , which highlights the common occurrence of multiple serotypes affecting herds in endemic countries. Additionally, one study in Pakistan, demonstrated detection and sequencing of two viruses from one sample with different serotypes (A and Asia-1), and another sample with two different sublineages of A/Iran-05 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple FMDVs in the same geotemporal space hinders disease control and may pose an increased risk of emergence of new strains. Numerous studies have reported serological evidence of infection with multiple serotypes within the same animal, which indicates evidence of cumulative, lifetime exposure (Eldaghayes et al., ; Ludi et al., ; Namatovu et al., ; Sikombe et al., ; Wungak et al., ). However, simultaneous coinfection is a distinct subcategory of multiple exposures and has been reported rarely in clinical samples from cattle (Jamal, Ferrari, Ahmed, Normann, & Belsham, ; Souley Kouato et al., ; Ullah et al., ; Wungak et al., ), but is believed to occur more frequently in oropharyngeal fluid samples from African Cape buffalo (Anderson, Doughty, Anderson, & Paling, ; Hedger, ; Vosloo et al., ).…”
Section: Introductionmentioning
confidence: 99%